2021
DOI: 10.3389/fpsyg.2021.665632
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Self-Oriented Empathy and Compassion Fatigue: The Serial Mediation of Dispositional Mindfulness and Counselor's Self-Efficacy

Abstract: Zhang et al. (2021), in their recent article exploring "the association between self-oriented empathy and compassion fatigue" (p. 1) stated that "Compassion fatigue (CF) is an empathetic reaction resulting from frequently witnessing the emotional or physical suffering of others or repeatedly listening to a person suffering from mental or physical dysfunction" (p. 1).If one returns to Davis' original Interpersonal Reactivity Index (IRI) scale development (Davis, 1983), the following is stated about the subscale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…While this study did not directly measure mindfulness and self-compassion, the results are consistent with literature suggesting that these factors play a crucial mediating role in the relationship between empathy and professional quality of life. For instance, Chapman (2021) found that dispositional mindfulness and self-compassion can enhance self-oriented empathy and reduce Compassion Fatigue among counsellors (Chapman, 2021). Incorporating mindfulness-based interventions could therefore be beneficial in fostering empathic concern while protecting against emotional exhaustion (Birnie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this study did not directly measure mindfulness and self-compassion, the results are consistent with literature suggesting that these factors play a crucial mediating role in the relationship between empathy and professional quality of life. For instance, Chapman (2021) found that dispositional mindfulness and self-compassion can enhance self-oriented empathy and reduce Compassion Fatigue among counsellors (Chapman, 2021). Incorporating mindfulness-based interventions could therefore be beneficial in fostering empathic concern while protecting against emotional exhaustion (Birnie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Positive Affect have been associated with increased resilience, improved coping strategies, and enhanced overall well-being (Zdun-Ryżewska et al, 2022). Moreover, Positive Affect can foster a more empathetic and compassionate professional demeanor, thereby enhancing the quality of care provided to clients and patients (Chapman, 2021).…”
Section: Introductionmentioning
confidence: 99%